The economies of Southeast Asia : - Tongzon, Jose L. (Northampton, MA, USA : E. Elgar, 1998)
The Economies of Southeast Asia provides a modern, aythoritative introduction to the economic development of the Association of Southeasdt Asian Nations (ASEAN). It evaluates the extent to which the phenomenal growth in the region is due to ASEAN cooperation.